In Defence of Anachronism - Pickavé, Martin (Laval théologique et philosophique, 2020)
In this short contribution I argue that the history of philosophy has much to gain from an engagement with the questions and conceptual tools of contemporary (analytic) philosophy. In particular I argue against the view that the historian of philosophy’s engagement with contemporary philosophy necessarily leads to anachronism. Whatever the risks of failure, they seem to be outweighed by the potential for insight. Advocates of a “purely” historical approach to the history of philosophy defend their approach by pointing to the idea that the history of philosophy can and should be studied on its own terms and independently of our current philosophical interests. I try to show that this is an illusion.